Komunitas makrozoobentos dan kaitannya dengan kualitas air aliran sungai Senggarang, Kota Tanjungpinang - Safitri, Aknes; Melani, Winny Retna; Muzammil, Wahyu (Universitas Malikussaleh, 2021)
Senggarang is one of the coastal villages in Tanjungpinang City which has a river that flows from the upstream downstream into the sea. The flow of the Senggarang river has distinctive characteristics that are commonly found in small island waters, namely having a relatively short upstream to downstream distance, and the downstream part is influenced by tidal conditions. Various activities along the Senggarang river flow would cause changes in water quality which would impact the presence of macrozoobenthic. The objective of this study was to determine the relationship between the macrozoobenthic community and the water quality of the Senggarang river. Macrozoobenthic sampling, and environmental parameters were carried out using random sampling methods. The results of this study were obtained 27 species from 6 phylum, namely phylum Arthropoda 13 species, phylum Ciliophora 3 species, phylum Echinodermata 1 species, phylum Mollusca 4 species, phylum Nematoda 5 species, and phylum Tardigrada 1 species. The average macrozoobenthic density is 172 ind./ m3 for freshwater and 704 ind./ m3 for brackish waters. The average diversity value for freshwater is 1.29 and 2.16 waters with medium salinity, the average uniformity value of 0.85 freshwater and 0.94 of high in brackish waters, the average dominance value of 0.32 freshwater and 0.13 of low in brackish waters. The relationship of macrozoobenthos with the quality of freshwater based on PCA analyses related to temperature and dissolved oxygen, in brackish waters to temperature, dissolved oxygen, and current.Keywords: Macrozoobenthic community, PCA, River flow, Water quality